Environmental management in mega construction projects - Yang, Jianming (Springer, 2017)
This book discusses environmental management and construction management approaches to the environmental problems that can emerge in construction projects. It sets a brand new standard for environmental management in mega construction projects in China and helps all construction project stakeholders establish a more compliant and efficient environmental management system. The authors systematically explore management systems and team management, offering managerial methods and tips based on international and Chinese practices. Outlining all the environmental challenges that can arise during construction, it is a valuable resource for company owners, construction contractors, and construction management consultants and companies. It also offers useful insights for engineers, project managers and project executives.
Keywords: Construction projects -- Environmental aspects.; Construction industry -- Environmental aspects.; Environmental impact analysis.; elektronické knihy; electronic books